Direito econômico e o contrato internacional de trabalho - Nazar, Nelson (2007)
This work has for target to demonstrate the autonomy of the Economic law and the peculiarities of the Law n.º 7.064/82. The subject justifies because the technological improvement, in special in the field of the telecommunications, diminished in the distance physical between the nations, what it facilitated and it contributed for the fortifying of the international business relations. With this, it had the birth companies multinationals, appearing the necessity of if establishing norms with intention to protect the Brazilian workers placed in the exterior. In regards to the aspects theoretician-metodologics, the present work was supported in the Brazilian jurisprudencial research and in the international organisms, as well as in the examination of different writers. As result of the research, was inferred that the Economic law represents an independent branch of the Law, with proper method, developed through pragmatic, flexible and formal criteria. With respect to act of contract of Brazilians to give services abroad, was verified that the Law n.º 7.064/82, at great length analyzed in the thesis, imposed a series of requirements to the companies whom they intend to carry through such negotiation, aiming at to guarantee to the employees the respect minimum rights and, over all, the worthy conditions of work